A Critical Approach to Investigating Communication Practices of Marginalized Populations Using Longitudinal Field Experiments. Issue 1 (2nd January 2020) - Read, Glenna L.; Partain, Laura P. B.; Vaughn, Zachary; Semivolos, Antonina; Anderson, Philip B.; Gonzales, Amy L.
ABSTRACT: Research on information and communication technologies conducted with a vulnerable sample consists of a unique host of challenges not experienced in research with oft-used student samples. This article suggests that field experiments, conducted through a self-reflexive critical studies lens, are one way that communication researchers may address some of these barriers while keeping in mind sensitivity to inherent power imbalances. While considering the ongoing debate regarding the use of student samples in communication research, this paper examines one longitudinal field experiment that investigated the role of stable ICT access on health outcomes. We discuss the power dynamics at play in the relationships between the primary investigator, research assistants, and participants as well as describe the tradeoffs that are considered in this type of work. The marrying of the positivistic approach of field experiment with a critical studies lens can benefit a growing body of scholarship from various epistemological traditions, invested in socially conscious research within marginalized communities. We provide a self-reflexive analysis of our study along with practical recommendations within the context of our challenges and successes.